The Effects of Computer-Assisted Instruction in Reading: A Meta-Analysis - Kunkel, Amy (University of Minnesota, 2015)
The purpose of this study was to investigate the effectiveness of computer-assisted instruction (CAI) to improve the reading outcomes of students in preschool through high school. A total of 61 studies met criteria for this review, and 101 independent effect sizes were extracted. Results indicated that the mean effects for students receiving reading CAI were small, positive, and statistically significant when compared to control groups receiving no treatment or non-reading CAI. Categorical moderator analyses and meta-regression were conducted to explore the variation in effects. Results of an analysis of research quality indicated that, on average, about half of quality indicators were met. The results of this meta-analysis show that CAI in reading can effectively enhance the reading outcomes of students in preschool through high school. Future, high-quality research should be conducted to identify effective programs and establish best practice in the instructional design of CAI to enhance the reading skills of all students.